Sound Velocity Measurements of B2‐Fe‐Ni‐Si Alloy Under High Pressure by Inelastic X‐Ray Scattering: Implications for the Composition of Earth's Core. Issue 15 (4th August 2022) - Dominijanni, S.; McCammon, C. A.; Ohtani, E.; Ikuta, D.; Sakamaki, T.; Ishii, T.; Criniti, G.; Dubrovinsky, L. S.; Khandarkhaeva, S.; Fedotenko, T.; Glazyrin, K.; Uchiyama, H.; et al.
Abstract: Elastic properties of B2‐Fe0.67 Ni0.06 Si0.27 (15 wt.% Si) alloy have been investigated by combined high‐resolution inelastic X‐ray scattering and powder X‐ray diffraction in diamond anvil cells up to 100 GPa at room temperature. Densities ( ρ ), compressional ( V P ) and shear ( V S ) wave velocities were extrapolated to inner core conditions to enable comparison with the preliminary reference Earth model. The modeled aggregate compressional and shear wave velocities and densities of the two‐phase mixture of B2‐Fe0.67 Ni0.06 Si0.27 and hcp ‐Fe‐Ni are consistent with inner core PREM values of V P, V S, and ρ based on a linear mixing model with 30(5) vol % B2‐Fe0.67 Ni0.06 Si0.27 and 70(5) vol % hcp Fe‐Ni, which corresponds to ∼3–5 wt.% Si and ∼5–12 wt.% Ni. Plain Language Summary: The composition of the inner core holds key information about how Earth evolved and how current processes such as the geomagnetic field work. Because the core cannot be directly sampled, our best estimates of its composition are based on the comparison of geophysical data with laboratory measurements of candidate materials. Decades of study have shown the inner core to be composed mainly of iron (with a minor amount of nickel) alloyed with one or more light elements, such as silicon. However, the effect of Si on the geophysical properties of Fe‐Ni alloys is not well established. In this study, we performed laboratory experiments to determine the density and sound velocity of Fe‐Ni‐Si alloy under extreme pressure conditions. We compared our results with seismological determinations and found that Earth's inner core can be accounted for by a mechanical mixture of cubic Fe‐Ni‐Si and hexagonal Fe‐Ni alloys. This mixture has a bulk composition of ∼3–5 weight % Si and ∼5–12 weight % Ni and is consistent with geophysical constraints. Key Points: Sound velocities and densities of B2‐Fe‐Ni‐Si alloy are determined at high pressure, up to 100 GPa, using inelastic X‐ray scattering and X‐ray diffraction Seismologically observed compressional and shear wave velocities and density of Earth's inner core can be accounted for by a two‐phase mixture of 30 vol % B2‐Fe‐Ni‐Si and 70 vol % hcp Fe‐Ni alloys Extrapolated results at inner core boundary conditions are consistent with an inner core composition containing ∼3–5 wt.% Si and ∼5–12 wt.% Ni